Aortic root dimensions are predominantly determined by genetic factors: a classical twin study - Celeng, Csilla; Kolossváry, Márton; Kovács, Attila; Molnár, Andrea Ágnes; Szilveszter, Bálint; Horváth, Tamás; Károlyi, Mihály; Jermendy, Ádám L.; Tárnoki, Ádám D.; Tárnoki, Dávid L.; Karády, Júlia; Voros, Szilard; et al. (European radiology, 2017)
Objectives Previous studies using transthoracic echocardiography (TTE) observed moderate heritability of aortic root dimensions. Computed tomography angiography (CTA) might provide more accurate heritability estimates. Our primary aim was to assess the heritability of the aortic root with CTA. Our secondary aim was to derive TTE-based heritability and compare this with the CTA-based results. Methods In the BUDAPEST-GLOBAL study 198 twin subjects (118 monozygotic, 80 dizygotic; age 56.1 ± 9.4 years; 126 female) underwent CTA and TTE. We assessed the diameter of the left ventricular outflow tract (LVOT), annulus, sinus of Valsalva, sinotubular junction and ascending aorta. Heritability was assessed using ACDE model ( A additive genetic, C common environmental, D dominant genetic, E unique environmental factors). Results Based on CTA, additive genetic effects were dominant (LVOT: A = 0.67, E = 0.33; annulus: A = 0.76, E = 0.24; sinus of Valsalva: A = 0.83, E = 0.17; sinotubular junction: A = 0.82, E = 0.18; ascending aorta: A = 0.75, E = 0.25). TTE-derived measurements showed moderate to no genetic influence (LVOT: A = 0.38, E = 0.62; annulus: C = 0.47, E = 0.53; sinus of Valsalva: C = 0.63, E = 0.37; sinotubular junction: C = 0.45, E = 0.55; ascending aorta: A = 0.67, E = 0.33). Conclusion CTA-based assessment suggests that aortic root dimensions are predominantly determined by genetic factors. TTE-based measurements showed moderate to no genetic influence. The choice of measurement method has substantial impact on heritability estimates. Key Points • Aortic root dimensions are determined by genetic and environmental effects. • Transthoracic echocardiography (TTE) demonstrated moderate to no genetic effects on aortic root dimensions. • Computed tomography angiography might provide more accurate heritability estimates compared to TTE. • Three-dimensional imaging techniques are needed to reliably quantify aortic root dimensions.